PENGEMBANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS BERBASIS KOMPUTER PADA PERUSAHAAN KECIL (STUDI KASUS PADA PT. TRUST TECHNOLOGY) - Rochmawati Daud; Valeria Mimosa windana (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The aims of this study to evaluate the performance of companies that are still using manual systems on sales activities and cash receipts which resulted in the presentation of cash receipts and sales report on PT. Trust Technology is becoming less effective, and providing advice to develop the company become a computer based system,that can improve the performance of the company to be more effective and efficient to produce cash receipts and sales reports.The results showed that there are still many weaknesses in information sales and cash receipts manual system in PT. Trust Technology, such as lack of control over the transaction receipt Â is still in the form of paper and very easily to lost or damaged, and double tasks between departments. This is some of problems experienced by the Â companies.To minimize the weaknesses of the company,the authors propose to develop sales and cash receipts computer-based information systems.